Profitabilitas Modal Ekuitas Pada Koperasi Wanita As Sakinah Sidoarjo - PUTRI RAGIL PURNANINGSIH (Universitas Negeri Surabaya, 2014)
Measuring of fund work is needed to measure cooperation’s succes to reach its goal. The goal are to improve member’s wealthy and ability to pay the debt. One of way to measuring fund work is the profitability of the equity. This research made to knowing Kopwan As Sakinah’s capital equity profitability and development of Kopwan As Sakinah profitability. Kind of this research is quantitative research and use descriptive research methode. Technical data collect use interview and documentation then analyzed by descrptive analysis technic and trend analysis. Result of this research show that capital equity profitability of Kopwan AS Sakinah that in 2009 its capital equity profitablity reach 44,6% with health criteria, in 2010 its capital equity profitability reach 31,1% with health criteria. Then decreasing in 2011 reach 11,9% with less health criteria, in 2012 reach 3,3% with unhealth criteria then increasing in 2013 reach 8,9% with unhealth criteria. While development of kopwan As Sakinah capital equity profitability based on trend analisys it has negative trend with result Y=19,8 – 10,08X. From that result its mean Kopwan As Sakinah capital equity always decrease 10,8X in every years. To solve that problem Kopwan As Sakinah should inform to members about Kopwan As Sakinah programs and build a solidarity among the Kopwan As Sakinah management and coordination to each Kopwan As Sakinah boards about Kopwan As Sakinah programs. Keywords :profitability, capital equity. Penelitian ini dibuat untuk mengetahui profitabilitas modal ekuitas Koperasi Wanita As Sakinah Sidoarjo dan mengetahui perkembangan profitabilitas modal ekuitasnya. Jenis penelitian ini adalah penelitian kuantitatif dengan metode penelitian yang digunakan adalah metode penelitian deskriptif. Teknik pengumpulan data dengan cara wawancara dan dokumentasi, selanjutnya data di analisis dengan teknik analisis deskriptif dan analisis trend. Hasil penelitian menunjukkan tingkat profitabilitas modal ekuitas Kopwan As Sakinah adalah sebagai berikut tahun 2009 profitabilitas modal ekuitas Kopwan As Sakinah mencapai 44,6% dengan kriteria sehat, tahun 2010 mencapai 31,1% dengan kriteria sehat, kemudian menurun pada tahun 2011 mencapai 11,9% dengan kriteria kurang sehat, tahun 2012 mencapai 3,3% dengan kriteria tidak sehat dan tahun 2013 naik pada angka 8,1% dengan kriteria tidak sehat. Sedangkan perkembangan profitabilitas modal ekitas Kopwan AS Sakinah berdasarkan analisis trend yang telah dilakukan, profitbilitas modal ekuitas Kopwan As Sakinah memiliki jenis trend negatif dengan hasil Y= 19,8 – 10,08X. Artinya profitabilitas modal ekuitas Kopwan As Sakinah selalu mengalami penurunan sebanyak 10,08X setiap tahunnya. Untuk mengatasi hal tersebut Kopwan As Sakinah dapat melalkukan penghematan biaya operasional, membangun kepercayaan anggota terhadap pengurus dan membangun solidaritas antar pengurus Kata kunci: profitabilitas, modal ekuitas.